Cytotoxic effect of endemic Tchihatchewia isatidea Boiss. from Turkey - Kirbag, Sevda; Keser, Serhat; Tekin, Suat; Inci, Sule; Sandal, Suleyman (Brill, 2021)
Tchihatchewia isatidea Boiss (Brassicaceae) is known among the public as Reddish Bride, Paint and Bridal Flower. Flower parts are used for painting and flowering branches for treatment of cough. In this study, anticancer properties of water, ethanol and methanol extracts of Tchihatch-ewia isatidea flower parts were investigated against human breast (MCF-7), human colon (HCT-116) and human prostate (LNCaP) cancer cell lines. Changes in the viability of cancer cells were de-tected by utilizing 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. Studies have shown that there is a statistically significant decrease in the cell viability of human breast cancer (MCF-7), colon (HCT-116) and prostate (LNCaP) cancer cells when extracts of T. isati-dea water, ethanol and methanol are used.
Keywords: Tchihatchewia isatidea; paint flower; medical plant; cytotoxic; MTT